2022
DOI: 10.1017/jgc.2021.3
|View full text |Cite
|
Sign up to set email alerts
|

The change over time of the perceptions of school counsellor candidates related to students with learning disabilities

Abstract: The purpose of this study was to examine the impact of training on learning disabilities (LD) on school counsellor candidates’ perceptions related to students with LD. The study group was comprised of 51 students in the Counselling and Psychological Guidance Department. The participants responded to an open-ended question: ‘Students with learning disabilities are like … Because …’. A content analysis technique was used in the analysis of the data. Based on the study results, it was determined that before being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…It is suggested in the study by Bildiren (2018) to use non-verbal intelligence tests for identifying gifted children in Turkey coming from lower socio-economic levels in addition to the development of non-verbal intelligence tests. In addition, it is reported that there are difficulties in identifying gifted children with learning difficulty and that it is necessary to apply non-verbal intelligence tests during this process (Bildiren & Fırat, 2020; Firat, 2021). It can be stated that the development of this test during the present study will make significant contributions to both identification and assessment before intervention.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested in the study by Bildiren (2018) to use non-verbal intelligence tests for identifying gifted children in Turkey coming from lower socio-economic levels in addition to the development of non-verbal intelligence tests. In addition, it is reported that there are difficulties in identifying gifted children with learning difficulty and that it is necessary to apply non-verbal intelligence tests during this process (Bildiren & Fırat, 2020; Firat, 2021). It can be stated that the development of this test during the present study will make significant contributions to both identification and assessment before intervention.…”
Section: Introductionmentioning
confidence: 99%